Renal coccidiosis in black skimmers in North America reveals an uncharacterized Eimeria lineage (Apicomplexa: Eimeriidae) - Kátia R. Groch; Tiana L. Sanders; Elena M. I. Duran; Dallas Clontz; Jacquelyn K. Grace; Raquel R. Rech; Guilherme G. Verocai; Laura K. Bryan (PLoS ONE, 2026)
Black skimmers ( Rynchops niger niger ) are New World coastal seabirds that breed along the Gulf of Mexico, southern Atlantic and Pacific coasts of the United States. Black skimmer populations are declining in North America, and little is known about health and diseases of this species. An outbreak of mortality causing the death of approximately 160 juvenile black skimmers occurred in the West Galveston and East Matagorda Bay populations during the 2022 and 2023 breeding seasons. Necropsy, histopathology, and molecular genetic methods were utilized to investigate the cause of morbidity in six chicks that died or were euthanized. The main gross findings included bilateral renomegaly with multiple pale tan foci. Characteristic histologic findings were granulomatous nephritis and cloacitis with intralesional coccidia. Various developmental stages including immature gamonts, microgamonts, macrogamonts, and oocysts were present extracellularly and in the cytoplasm of epithelial cells of distal tubules, medullary collecting ducts, ureters, and cloacal epithelium. A few oocysts were in the cytoplasm of multinucleated giant cells. Additionally, schizonts were observed in the small intestine of one case. Genetic analysis of partial 18S rRNA gene revealed a previously uncharacterized Eimeria lineage affecting kidney and cloaca and another Eimeria lineage affecting the small intestine. To the best of our knowledge, this is the first report of Eimeria infection in the genus Rynchops . The significance of renal and intestinal coccidiosis in black skimmers is unknown; however, in the present work it appeared to cause morbidity and likely contributed to the recent mortality outbreak.